An integral approach to address Chagas disease - Gold, Marina; Hermida, Maria Julia (Frontiers in Parasitology, 2023)
Chagas is a zoonotic disease conditioned by the need to eliminate or control the vector in human settlements before targeting infected individuals. Simultaneously it is necessary to raise awareness of health problems generated by chronic Chagas disease (ChD), for people to participate actively in vector control programs that will then enable the implementation of screening, treatment and follow-up strategies. Therefore, it is essential to engage the participation of the community in holistically designed integral programs to address ChD in all its complexity. This Perspective presents the case of Chagas management programs in the Department of General Taboada, Province of Santiago del Estero, Argentina, to showcase a possible strategy in vector control, diagnosis and treatment programs that integrate ChD into the local public health system and engage community participation. Through this Perspective we argue for the importance of the contribution of social science methodologies and epistemologies in the process of integrating ChD into the public (and primary) health care system.